Responses of some genotypes of bio-fortified climbing common bean (Phaseolus vulgaris L.) to the climatic conditions of three agro-ecological zones, southern DR Congo - Ilunga, Tshibingu Meschac; Assani Bin Lukangila, Mick; Ilunga Maloba, Maki; Kanyenga Lubobo, Antoine (2017)
Multi local trials were carried out during the 2014-2015 cropping season simultaneously in three sites: Kasenga, Katanga and Fungurume located in the provinces of Upper Katanga and Lualaba. Five genotypes of bio-fortified climbing common bean: NUC 479, CWARENTINO, NAMULENGA, M 211, CODMLV059 were sown according to the randomized complete block design with four replications. The ecological conditions of Katanga site were more or less lenient to justify the high yield of seed, it should be noted that GWARENTINO and NAMULENGA varieties showed a high productivity. Furthermore, the combination of genotypes x environment revealed interactions on all parameters, yields were low for all genotypes due to poor rainfall distribution, but NUC479 remained least influenced by the environment. This could be exploited in varietal improvement program face to water stress, while keeping the other materials in the germplasm.